OPTIMALISASI BIAYA PENDISTRIBUSIAN TAHU PADA PERUSAHAAN TAHU BERIKA: Case Study: Tahu Berika Company, Laleten Village, Weliman District, Malacca Regency 2023 - Oktovianus Nahak; Oktovianus Sikas; Faustinus Luan; Leonardus Obe (Journal of Mathematics Theory and Applications, 2024)
This study aims to find out how to optimize the cost of distribution t ahu, with the Nort West Corner method and the Stepping Stone method in t ahu Berika companies. To find out how distribution costs compare before and after conducting research on tahu Berika companies. The transportation method is one of the methods used to find the cheapest way to distribute products from several sources (distribution centers, warehouses) to several destinations so that total transportation costs are minimized. The conclusions obtained from this research are as follows: The cost of distributing tofu using the Nort West Corner method as an initial solution for Berika tofu companies in March 2023 is; while the cost of distributing tofu using the Stepping Stone method as the final solution to Berika tofu companies in March 2023 is by using the Nort West Corner method as the initial solution and the Stepping Stone method as the final solution, the total minimum distribution costs obtained by each of them are  and while the calculations made by the company know Berika before using the Nort West Corner method and the Stepping Stone method are as large as.  With the savings in distribution costs of each is as large as and